An Online English Practice System Based on Diagnosis Learning and ASP.NET - Wang, Bin; Guo, Lina (International Conference on Measuring Technology and Mechatronics Automation (Print), 2022)
In the online learning system, there is a lack of teachers to evaluate the learners' learning status, and the learners' learning efficiency is not high. To solve such problem, this paper analyzes the data collected in the practice process of CET-4, and realizes a network-based diagnostic evaluation model. We construct a knowledge system for assignment in exercise database, then use logistic function model to diagnose learners' ability value. Then, the logistic function model is used to diagnose the learners' ability value, and the difficulty value of the exercise is deduced. At last, the detailed scheme is provided by combining the functional modules and database structure of the system, and the specific system operation and analysis are provided with .NET + MVC. The experimental results show that our system can better diagnose the learners' weakness in question type, and provide better practice guidance and test recommendation according to their learning status and knowledge point question type obstacles, to improve the learners' learning level and examination ability.